The world of rare interstitial lung diseases - Buschulte, Katharina; Cottin, Vincent; Wijsenbeek-Lourens, Marlies; Kreuter, Michael; Diesler, Rémi (European respiratory review, 2023)
The world of rare interstitial lung diseases (ILDs) is diverse and complex. Diagnosis and therapy usually pose challenges. This review describes a selection of rare and ultrarare ILDs including pulmonary alveolar proteinosis, pulmonary alveolar microlithiasis and pleuroparenchymal fibroelastosis. In addition, monogenic ILDs or ILDs in congenital syndromes and various multiple cystic lung diseases will be discussed. All these conditions are part of the scope of the European Reference Network on rare respiratory diseases (ERN-LUNG). Epidemiology, pathogenesis, diagnostics and treatment of each disease are presented. - Tweetable abstract ERSpublications - click to tweetMany rare and ultrarare ILDs are underdiagnosed. Increasing insight into pathobiology, genetics and disease behaviour have led to better treatment options. Early consultation with or referral to expert centres (ERN-LUNG) is advised. https://bit.ly/3vwYrib
Gesehen am 27.04.2023